2008
DOI: 10.1542/peds.2007-3178
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Hypersensitivity Reactions to Cephalosporins in Children

Abstract: Extremely few nonimmediate manifestations associated with cephalosporin therapy are actually hypersensitivity reactions, whereas most immediate reactions to cephalosporins are IgE-mediated. Cephalosporin skin testing is a useful tool for evaluating such reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 26 publications
7
61
2
1
Order By: Relevance
“…Most are non-immediate cutaneous reactions, occurring >1 h following administration of a dose, of mild to moderate severity, in children below 4 years of age [226,227,229]. There are no predisposing risk factors for beta-lactam allergy in children, and only a minority (7-16%) of children with suspected beta-lactam hypersensitivity are found to be allergic following investigation [225,230].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Most are non-immediate cutaneous reactions, occurring >1 h following administration of a dose, of mild to moderate severity, in children below 4 years of age [226,227,229]. There are no predisposing risk factors for beta-lactam allergy in children, and only a minority (7-16%) of children with suspected beta-lactam hypersensitivity are found to be allergic following investigation [225,230].…”
Section: Epidemiologymentioning
confidence: 99%
“…The role of specific IgE in children with immediate reactions to beta-lactams requires further evaluation [229]. In children with non-immediate reactions, measurement of specific IgE is not useful [225].…”
Section: Specific Igementioning
confidence: 99%
See 1 more Smart Citation
“…5 Studies generally have shown low sensitivity and positive predictive value. 64,65 Nevertheless, skin test for BL hypersensitivity is still considered 'good' by the International Consensus in 2014. 60 Patients with negative cephalosporin skin test should pass a DPT before finally receiving a cephalosporin.…”
Section: Ten Per Cent Cross-reactivity: An Over-estimationmentioning
confidence: 99%
“…Ceftriaxone is a third-generation cephalosporin antibiotic that has broad spectrum activity against Gram-negative and Gram-positive bacteria (2). Although ceftriaxone administration has been associated with various allergic reactions such as urticaria, angioedema, edema, erythema, maculopapular rash and anaphylactic shock (2,3), to the best of our knowledge, there is no report about whether ceftriaxone gives rise to allergenic acute coronary syndrome or not. Here, we define a case of severe CAS, culminating in acute inferior myocardial infarction (MI), as the result of an acute allergenic reaction, which was likely related to ceftriaxone use.…”
Section: Introductionmentioning
confidence: 99%